2009
DOI: 10.1371/journal.pone.0004137
|View full text |Cite
|
Sign up to set email alerts
|

IL2RA/CD25 Gene Polymorphisms: Uneven Association with Multiple Sclerosis (MS) and Type 1 Diabetes (T1D)

Abstract: BackgroundIL-2 receptor (IL2R) alpha is the specific component of the high affinity IL2R system involved in the immune response and in the control of autoimmunity.Methods and ResultsHere we perform a replication and fine mapping of the IL2RA gene region analyzing 3 SNPs previously associated with multiple sclerosis (MS) and 5 SNPs associated with type 1 diabetes (T1D) in a collection of 798 MS patients and 927 matched Caucasian controls from the south of Spain. We observed association with MS in 6 of 8 SNPs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 32 publications
4
34
2
4
Order By: Relevance
“…9 In families with systemic lupus erythematosus (SLE), other autoimmune diseases, such as MS and RA, occur more frequently than in the general population. 10 Such observations suggest the presence of shared genes and involvement of common disease pathways, and are supported by a number of reports on genes that are associated with more than one autoimmune disease, such as PTPN22 in RA and SLE, 11 IRF5 in MS, 12 RA 13 and SLE, 14 and more recently IL2RA/CD25 in T1D 15 and MS, 16 though with a different risk allele.…”
Section: Introductionmentioning
confidence: 64%
“…9 In families with systemic lupus erythematosus (SLE), other autoimmune diseases, such as MS and RA, occur more frequently than in the general population. 10 Such observations suggest the presence of shared genes and involvement of common disease pathways, and are supported by a number of reports on genes that are associated with more than one autoimmune disease, such as PTPN22 in RA and SLE, 11 IRF5 in MS, 12 RA 13 and SLE, 14 and more recently IL2RA/CD25 in T1D 15 and MS, 16 though with a different risk allele.…”
Section: Introductionmentioning
confidence: 64%
“…24,25 There is also emerging data suggesting that one of the associated SNPs at the IL2RA locus confers differing risk and protective effects for T1D and multiple sclerosis. 26,27 JIA is a phenotypically heterogeneous disease and can be classified into more clinically homogeneous diseases using the ILAR classification criteria (Supplementary Table 1). 28 However, comparing each of the ILAR subtypes separately against controls would result in a large number of hypothesis tests.…”
Section: Resultsmentioning
confidence: 99%
“…41 This SNP is also in strong LD with rs10795791 and rs4147359 (HapMap r 2 ¼0.93 and 0.72, respectively), which were shown to be associated both with MS and T1D. 12 Regarding rs2256774, it was found associated to higher levels of rubella antibody 42 and is in strong LD (HapMap r 2 ¼0.63) with rs11594656, which was shown to be correlated with IL2RA expression. 13,15 These studies only considered single-SNP effect and did not take into account the genetic complexity of IL2RA effect.…”
Section: Discussionmentioning
confidence: 92%
“…12,13 Moreover, functional studies showed that rs2104286 was associated with differences in surface expression of level proteins, 13 and in levels of a soluble form of IL-2 receptors. 14,15 However, when an association signal has been obtained on a SNP, there is still a long way before identifying the causal variants, and deciphering their mode of action and their connection with the other pieces of the pathway.…”
Section: Introductionmentioning
confidence: 99%